Anxiolytic Effect of Citrus aurantium L. in Crack Users. (18th October 2017) - Chaves Neto, Gabriel; Braga, João Euclides Fernandes; Alves, Mateus Feitosa; de Morais Pordeus, Liana Clébia; Santos, Sócrates Golzio dos; Scotti, Marcus Tullius; Almeida, Reinaldo N.; Diniz, Margareth de Fátima Formiga Melo
Abstract : The objective of this study was to investigate the anxiolytic effects of the essential oil (EO) of Citrus aurantium L. in patients experiencing crack withdrawal. This was developed with internal users in therapeutic communities in Paraíba, Brazil. The test population consisted of 51 volunteers, subdivided into three groups. To elicit anxiety, the Simulated Public Speaking (SPS) method was used. Physiological measures were assessed at specific phases during the experiment using appropriate equipment. Psychological measures of anxiety were assessed using the Trait-State Anxiety Inventory (IDATE) and the Analog Smoke Scale (HAS). EO was administered by nebulization. The experiment was developed in individual sessions and consolidated to four phases. The results demonstrated that the test subjects in the groups that were given the EO maintained controlled anxiety levels during SPS, when compared to the Control Group (no treatment). Subjects who used the EO also maintained levels of "discomfort" and "cognitive impairment" during SPS. It was concluded that individuals who are experiencing internal crack cocaine withdrawal present high anxiety traits and that nebulization of the EO of Citrus aurantium L. provided an acute anxiolytic effect in crack cocaine users exposed to SPS.